The Relationship Between Student’s Creativity and Learning Achievement on The Topic Wave, Vibration and Sound - Eka Nur Setyaningsih; Widha Sunarno; Joko Arianto (Universitas Sebelas Maret, 2022)
Creativity is one of the factors that influence learning outcomes, including affective, cognitive and psychomotor aspects. The purpose of this study was to determine student creativity and learning outcomes the relationship and influence between the two on the material of wave and sound vibrations. This research is non-experimental quantitative research. The subjects of this study were 32 students of class VIII SMPN 1 Sambi. Instruments in the form of questionnaires, self-assessment, cognitive and psychomotor test questions. Proof of hypothesis is tested for normality and linearity, correlation and simple regression tests. The results showed that the creativity of eighth-grade students of SMPN 1 Sambi was67.The results of the correlation coefficient between creativity with affective, cognitive, and psychomotor learning outcomes, respectively 0.308, -0.370 and -0.492 and a contribution of 10 %, 20% and 24% The conclusions in this research are creativity and student learning outcomes are included in the moderate category, there is a weak correlation and significant negative influence between creativity with cognitive and psychomotor learning outcomes of students. The implication is that student creativity increases but is not matched by an increase in student learning outcomes, both psychomotor and cognitive..